A rare case of recurrent acute pancreatitis after EUS-FNA in a patient with pancreatic intraepithelial neoplasia type 2 - Celso Ardengh, José (2019)
Pancreatic intraepithelial neoplasia (PanIN) is considered a pre-malignant lesion difficult to identify by imaging methods. EUSFNAis an effective technique to obtain material for histopathological study of pancreatic cystic tumors, but it is not free ofadverse events. We report a case of a 56 years old patient, with chronic abdominal pain (early 1994). MRI showed pancreaticcystic images. The etiologic diagnosis was doubtful and EUS-FNA was performed. Immediately after a FNA, patient had anepisode of acute pancreatitis, requiring hospitalization. During one year after FNA he had five episodes of AP. A new EUSsuspected of PanIN, which was confirmed by surgery. After surgery the patient is well and has no more episodes of AP. Althoughthe risk of AP, EUS-FNA should be performed to determine the best treatment for these patients with chronic abdominal painwho have cystic changes of pancreatic gland.